Air Conditioning Energy Efficiency and Thermal Comfort in Hotel Buildings in Hot and Humid Tropical Climates: The Case Study of Makassar City Coastal Area Hotel, South Sulawesi, Indonesia - Nasrullah, Nasrullah; Hamdy, Muhammad Awaluddin (Engineering, technology & applied science research, 2024)
The objective of this research is to examine energy consumption efficiency strategies with respect to the type of dwelling unit, cooling load, and thermal comfort. This can be evaluated through the study of the hotel building air system, with the aim of ensuring the thermal comfort of its occupants. This research employs a quantitative methodology, using observation, measurement, and experimental techniques. The case study is situated within the context of hotels in Makassar City, South Sulawesi Province, Indonesia. The subject of this study is the Swissbel Hotel building, located in the coastal area of Makassar City. The data are analyzed in order to determine the Energy Consumption Intensity (IKE), Room Energy Intensity (REI), and occupancy rate based on the heat load inside and outside the building.  The data are then processed using a parametric statistical approach. Subsequently, the building envelope is analyzed through the calculation of the Overall Thermal Transfer Value (OTTV) in accordance with the standards set out in SNI 6390: 2011. The cooling load and a thermal comfort assessment, in line with the Predicted Mean Vote (PMV) index, Predicted Percentage of Dissatisfaction (PPD) index, and effective temperature according to the ASHRAE 55-2022 standard, are then calculated, and a simulation is performed to determine the most efficient strategy for the use of air conditioning energy. The findings indicated that alterations in the dimensions of the facade (sun shading) resulted in a 16% reduction in the cooling load, with the incorporation of horizontal and vertical shading sizes of 4 m × 2.5 m, square glass openings, and 8 mm heat-absorbing glass. This led to a PMV value of 0.40, a PPD of 8%, and an effective temperature value of 26.8°C. The modification resulted in a percentage gain of 20.08%, at 10-60% occupancy load with a cooling load reduction rate of 1,912,071 kW and a thermal comfort index within the comfortable range.